Growth of Solutions of Some Linear Difference Equations with Meromorphic Coefficients (Communications in Mathematical Research, 2020)
In this paper, we investigate the properties of solutions of some lineardifference equations with meromorphic coefficients, and obtain some estimates ongrowth and value distribution of these meromorphic solutions.